STUDI KINETIKA REAKSI EPOKSIDASI MINYAK SAWIT - Revina Allundaru; Tanty Wisley Sitio; Setia Budi Sasongko (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Epoxidized triglycerides as a product of epoxidation have found important applications as plasticizers and additives for polyvinyl chloride (PVC). The raw material usually used is natural oil based. The usage of this raw material can give negative effects, one of them is the non-degradable characteristic. In addition, natural oil is non-renewable resources and the usage of raw material based from natural oil can increase the CO2 emission.According to the reasons above, renewable and bio-degradable alternative resources start to be found. One of this resources is plant oil and this research concern to epoxidation of plant oil. Plant oil which is used in this research is palm oil. In this research, we are going to study the influence of reaction time and temperature to the epoxide value, and reaction kinetics parameters.Palm oil was characterized with an iodine value of 58,37%w/w was in situ epoxidized by hydrogen peroxide and formic acid and the presence of benzene to reduce oxirane ring opening. Then the product was distillated to separate the epoxidized oil from the dissolved solvent. The epoxidized oil was neutralized by washing it twice in hot aquadest for 15 minute to remove the remaining acid compound.Palm oil epoxidation kinetic is known from the formation on epoxide compound during the reaction time. The rate constant of reaction at 30oC was 1,523864 x10-4 l/mole sec, at 40oC was 1,01755 x 10-5 l/mole sec, and at 50oC was 3,353358 x 10-4 l/mole sec. The activation energy of the palm oil epoxide formation was 29,391 kJ/mole. The conclusion of this research is that palm oil can be used as raw material to produce epoxide compound, this was identified by the epoxide value.